1994
DOI: 10.1143/jjap.33.786
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Low Resistance Base Ohmic Contact with Pt/Ti/Pt/Au for High-fmax AlGaAs/GaAs Heterojunction Bipolar Transistors

Abstract: Ohmic contacts to 500-Å-thick p-Al0.1Ga0.9As layer formed with a Pt/Ti/Pt/Au metal system were investigated. An extremely low contact resistivity of 4.2×10-7 Ω ·cm2 was obtained. The contact resistance increased with the increment of the Pt thickness, because the thicker the intermetallic layer becomes the thinner the AlGaAs layer beneath it, which leads to a higher contact resistance. The optimum Pt thickness was around 50 Å. Moreover, this metal scheme was thermally stable at 350° C. A high f … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…These particular metals were chosen, since they are commonly used for ohmic contacts in III-V materials. [2][3][4][5][6] Pt and Ti tend to have a fairly smooth diffusion profile when annealed at our maximum processing temperature of 300°C. [2][3][4] Although Pd and Au have rougher diffusion profiles, some work has indicated that if they are thin enough, they may also be used.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…These particular metals were chosen, since they are commonly used for ohmic contacts in III-V materials. [2][3][4][5][6] Pt and Ti tend to have a fairly smooth diffusion profile when annealed at our maximum processing temperature of 300°C. [2][3][4] Although Pd and Au have rougher diffusion profiles, some work has indicated that if they are thin enough, they may also be used.…”
Section: Introductionmentioning
confidence: 83%
“…[2][3][4][5][6] Pt and Ti tend to have a fairly smooth diffusion profile when annealed at our maximum processing temperature of 300°C. [2][3][4] Although Pd and Au have rougher diffusion profiles, some work has indicated that if they are thin enough, they may also be used. 5 Furthermore, Pt is an excellent diffusion barrier to Au at our processing temperature of 300°C, provided it is thick enough to avoid pinholes or other defects, so Au can be used as the top metal for all of the subsequent interconnects.…”
Section: Introductionmentioning
confidence: 83%
“…An InGaAs layer was adopted as a cap layer to reduce the emitter contact resistance. By using Pt/Ti/Pt/Au base metal, low contact resistivity of 8 x 10-7 Clcm2 was obtained [6]. Figure 1 shows the RF performance of the HBT.…”
Section: Technologies Of Aigaadgaas Hbt'smentioning
confidence: 99%